Textologial Study Of Al-Qur’an Manuscript : Rasm’s Study of The Manuscript From The H Ahmad Ibrahim Collection - Luluk Indah Kholifatin; Muhammad Bimo Wijoyo; Aisyatun Najwa Az-zahra (Journal of Islamic Education, 2026)
This study aims to determine the characteristics of rasm in the mushaf by H. Ahmad Ibrahim and its conformity with the Indonesian standard Ottoman rasm, as well as the forms of local adaptation that emerged in its writing. The study uses a qualitative method with a descriptive-analytical philological approach, through direct review of digital manuscripts in the DREAMSEA repository and a literature review related to rasm and codicology. The results show that the mushaf by H. Ahmad Ibrahim applies some of the rules of Ottoman rasm such as hadzf, ziyadah, badal, hamzah, and washlu-fashlu, but predominantly uses rasm imla'i in a number of words. This finding confirms the existence of creative local adaptation practices without completely abandoning the framework of Ottoman rasm. This study contributes to broadening the understanding of the plurality of traditions of copying the mushaf and enriches the study of the philology of the Qur'an in the Nusantara, especially in South Sulawesi.